Analysis of Covid-19 Export-Import and Business Obstacles between Indonesia and Japan - Hetami, Adietya Arie; Aransyah, Muhammad Fikry; Putri, Aprillia Pratiwi; Annisafazzahra, Annisafazzahra; Nurhidayah, Aprianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This paper aims to determine how Covid-19 affects import-export activities and the business between Indonesia and Japan. The method used to collect data is a qualitative method through literature study, namely by collecting and conducting a review of literature, documents, and the results of previous relevant studies. The data obtained from several sources are data on GDP (Gross Domestic Product) and data on exports and imports of the country concerned. In conducting the analysis, the technique used is data reduction, displaying data through graphs and tables and drawing conclusions from the data that has been obtained. The results are that some decreases and increases occurred during 2019-2021. However, the most significant decline occurred when Indonesia and Japan underwent a policy lockdown. The efforts to avoid the Covid-19 outbreak have significantly impacted the two countries' economic activities, dependent on export and import activities. However, the situation returned to normal due to the efforts made by both countries to restore the economy.